Root associated fungi in Arctic Glacier Forlands raw sequences - Eidesen, Pernille Bronken; Botnen, Synnøve S.; Mundra, Sunil; Kauserud, Håvard (Zenodo, 2020)
Climate change causes Arctic glaciers to retreat faster, exposing new areas for colonization. Several pioneer plants likely to colonize recent deglaciated, nutrient-poor areas depend on fungal partners for successful establishment. Little is known about general patterns or characteristics of facilitating fungal pioneers and how they vary with regional climate in the Arctic. The High Arctic Archipelago Svalbard represents an excellent study system to address these questions, as glaciers cover ∼60% of the land surface and recent estimations suggest at least 7% reduction of glacier area since 1960s. Roots of two ectomycorrhizal (ECM) plants ( Salix polaris and Bistorta vivipara ) were sampled in eight glacier forelands. Associated ECM fungi were assessed using DNA metabarcoding. About 25% of the diversity was unknown at family level, indicating presence of undescribed species. Seven genera dominated based on richness and abundance, but their relative importance varied with local factors. The genus Geopora showed surprisingly high richness and abundance, particularly in dry, nutrient-poor forelands. Such forelands will diminish along with increasing temperature and precipitation, and faster succession. Our results support a taxonomical shift in pioneer ECM diversity with climate change, and we are likely to lose unknown fungal diversity, without knowing their identity or ecological importance.